Delayed presenting traumatic Extradural Haematoma- whether surgery always necessary? – An experience in a tertiary care hospital. - Ghosh, Partha; Roy, Kaushik; Saha, Suniti Kumar; Nadkarni, Abhishek; Dixit, Sourabh (Asian Journal of Medical Sciences, 2018)
Background: Extradural haematoma (EDH), considered being the most serious preventable complication of head injury, requiring immediate diagnosis and surgical intervention. Though surgical evacuation constitutes the definitive treatment of this condition but many patients who presented late to emergency can be saved from craniotomy with watchful repeated neurological assessments. Aims and Objectives: To evaluate the role of surgical and non surgical management of delayed presenting traumatic EDH at a tertiary care Hospital. Materials and Methods: This study was conducted from December 2015 to February 2017 at Nil Ratan Sircar medical College, Kolkata. A total 100 cases of traumatic Extradural Haematoma were admitted with history of prior head injury of greater than 8 hours duration. All the patients were assessed clinically on admission and by NECT brain either prior to or immediately after admission. All patients with traumatic EDH were evaluated by dedicated trauma team and by Neurosurgeons, patients who came to hospital facility with more than 8 hours history of incident with haematoma <30 cm3, no associated midline shift and no signs of focal neurodeficits or papillary asymmetry with GCS 13-15, were initially managed conservatively, those who failed any of the chosen criteria treated by operative interventions. Results: Of all patients more 50% cases were associated with vehicular accident. Eighty percent cases were referred from primary or secondary care level hospitals and the remaining directly from accident site or scene of injury. Fifteen patients had post injury seizures, most of the cases were associated with additional intradural lesions like contusions or intracerebral haematoma. Approximately one forth patients presented with GCS >13, all these patients experiences positive outcomes. In this series of EDH location was temporoparietal region constitute 45% of the total, in 36 % of cases there were associated skull fracture. 55% of the patients in this series underwent operative intervention and 45% treated non operatively. Overall, 78% patients had good recovery, whereas 12% patients remained moderate to severe disabled at 6 weeks follow up period. Conclusion: Although surgical management is the treatment of choice in EDH, in selected delayed presenting EDH patients can be managed non-operatively with good outcome. Asian Journal of Medical Sciences Vol.9(4) 2018 41-45